PERAN KETELADANAN ORANG TUA DALAM PEMBENTUKAN KARAKTER DAN MENCEGAH PERILAKU BULLYING DI SD BEKASI JAYA V - Agnes Eka Septi; Suharjuddin; Yohamintin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the high number of bullying cases among elementary school students, which is a serious problem and requires immediate attention. Not only schools play a crucial role, but parental involvement is also crucial. The purpose of this study is to examine the role of parents in shaping children's character in responding to bullying. The method used is qualitative. The results show that parents play a vital role in shaping children's character because they are the first figures who serve as role models for children in behavior. Parents can shape children's character by providing good examples, cultivating positive behavior, effective communication, and inviting children to participate in household activities. By developing character from an early age, children will become more confident, resilient, and able to interact with their surroundings. In dealing with bullying, parents should instill courage and self-confidence in children, help children choose the right friends, and give them permission to defend themselves or even retaliate if treated badly.